(untitled) (International Journal of Ayurveda and Pharma Research, 2023)
A good voice is the basic need of humans. For professional voice users, voice governs their livelihood and social attraction. A good singing voice is attained by the regular vocal exercises and vocal training. Singing involves the skills like respiration, phonation, resonance and articulation. Bhramari Pranayama (BP) involves both humming and respiration. Humming is the resultant of the activity vocal structures which may have effect on the quality of the voice. Aim: To evaluate the effect of Bhramari Pranayama (BP) on voice quality Settings and Design: The study is an open clinical trial involving 30 healthy prospective singers fulfilling the inclusion and exclusion criteria, consenting for the study, who were enrolled through a survey in music schools in the region of Belagavi, Karnataka. Methods and Material: The voice of the 30 healthy prospective singers was recorded using PRAAT software with standard vocal tasks on day 0 of the study. Participants practiced 21 cycles of Bhramari Pranayama in the morning for 30 days. On Day 30, after the practice the voice was re-recorded with same vocal tasks and standard operative procedures being maintained. The recorded voice samples were saved and were subjected for voice analysis using softwares PRAAT, Vaghmi, CSL at AIISH, Mysuru. Statistical analysis used: Statistical analysis was done using SPSS 21 and Paired ‘t’ test was applied to derive the results. Statistical Significance was set up at p<0.05. Results: Bhramari pranayama showed highly significant results in the root mean square values of the Singing power ratio - SPR (p<0.01) and singing power difference (p<0.01). Significant results in the lowest value of the singing amplitude (p<0.05), singing amplitude range (p<0.01) and mean formant frequency of second formant of vowel /u/(p<0.05). Conclusion: Bhramari Pranayama improved the resonance characteristics of the voice and there by improved the quality of singing voice in prospective singers.